Development of Mobile Messaging Application Using Wifi Technology: A Study in Promoting Classroom Participation and Interaction - Gan, Chin Lay (2006)
The goal of this qualitative paper was to conduct a study to promote classroom participation and interaction using a mobile messaging application that enable students to send messages to instructor using mobile services. The study focused on the interaction between instructor and students. Barriers and challenges to students and instructor interaction are outlined based on literature reviews and observation studies. Results from the experiment shows that mobile messaging application promotes participation and increases interaction between students and instructor. Clear guidelines on use of mobile messaging application in classrooms must be drafted and enforced for successful implementation in promoting students and instructor interaction.